Ketamine Administration Leads to Learning-Memory Dysfunction and Decreases Serum Brain-Derived Neurotrophic Factor in Rats - Li, Miao; Xie, Aiming; Liu, Ya; Zeng, Qian; Huang, Shucai; Huang, Qiuping; Shao, Tianli; Chen, Xinxin; Liao, Zhenjiang; Cai, Yi; Xiao, Zhijie; Zhang, Xiaojie; et al. (Frontiers in Psychiatry, 2020)
Objective: This study investigated the effects of acute or chronic ketamine administration on learning and memory function as well as levels of brain-derived neurotrophic factor (BDNF) in the hippocampus and blood in order to explore the potential correlation between learning-memory dysfunction and ketamine. Methods: Rats were treated with 25 mg/kg ketamine for 3 d (n = 20) or 14 d (n = 20). Saline-treated rats were used as controls. The Morris water maze test was used to evaluate spatial learning and memory after 10 d of withdrawal. The level of BDNF in serum and the hippocampus were measured by ELISA. Results: The number of platform crossings and residence time in the sixth quadrant were significantly reduced in ketamine 3 d and 14 d groups than in the saline controls (both p < 0.05). In addition, the average escape latency of ketamine 3 d and 14 d groups were significantly longer than that of the saline 3 d and 14 d groups (p < 0.0001), respectively. Further examination found that only serum samples from ketamine 14 d group showed significantly decreased BDNF level compared to that from saline 14 d groups (p < 0.05). However, no differences were detected in hippocampus samples. Conclusion: Chronic ketamine exposure (25 mg/kg) causes spatial learning and memory deficits in SD rats, which may be associated with decreased serum BDNF levels.